Islamic Philanthropy and Empowerment: The BTQ For Leaders Model at PPPA Daarul Quran - Aflah, Kuntarno Noor (ZISWAF, 2025)
This study aims to analyze the community empowerment model within the Beasiswa Tahfidz Qur'an (BTQ) for Leaders program, developed by LAZNAS PPPA Daarul Qur'an for Qur'an memorization students in Yogyakarta and Central Java. This research employed a qualitative approach. Data were collected through seven years of observation and researcher involvement, interviews with stakeholders, and document studies. The data were then analyzed using an in-depth descriptive qualitative method. The findings indicate that the educational empowerment model implemented by LAZNAS PPPA Daarul Qur'an is highly unique and distinct from other models in the education sector. It encompasses skill development, strengthening of religious knowledge, control of Qur'anic memorization, empowerment training, and a mandatory one-year dedication period after graduation. This model proves to be highly effective for underprivileged families who aspire to pursue higher education while memorizing the Qur'an. Consequently, it produces hafidz and hafidzah (male and female Qur'an memorizers) who are prepared to become future leaders. Furthermore, this scholarship program enhances the welfare of its recipients, as individuals with high education and sufficient life provisions are well-positioned to improve their families' future socioeconomic status.